2000
DOI: 10.1021/la9916528
|View full text |Cite
|
Sign up to set email alerts
|

Compensation Effect for the Kinetics of Adsorption/Desorption of Gases/Vapors on Microporous Carbon Materials

Abstract: Preliminary studies of adsorption kinetics on activated carbon provided some tentative evidence for a possible compensation effect where the activation energies and ln(preexponential factors) obtained from the Arrhenius equation obey a linear correlation. However, a detailed analysis was not carried out. The adsorption characteristics of a series of n-alcohol vapors on the activated carbon BAX950 were investigated over the relative pressure range p/p o ) 0-0.97, for temperatures in the range 288-318 K. These d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

13
57
0
3

Year Published

2004
2004
2021
2021

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(73 citation statements)
references
References 46 publications
13
57
0
3
Order By: Relevance
“…Studies have shown that EEC also occurs during the adsorption of low molecular weight gases on active surfaces (Burevski et al 1991;Fletcher and Thomas 2000;Garrone et al 2008;Korolev et al 2011;Hercigonja and Rakić 2013;Pera-Titus 2016;Zukal et al 2009;Kelut et al 2014), wherein the dependence isn't necessarily linear, as Eq. (1) in unequivocal manner (Fletcher and Thomas 2000;Garrone et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Studies have shown that EEC also occurs during the adsorption of low molecular weight gases on active surfaces (Burevski et al 1991;Fletcher and Thomas 2000;Garrone et al 2008;Korolev et al 2011;Hercigonja and Rakić 2013;Pera-Titus 2016;Zukal et al 2009;Kelut et al 2014), wherein the dependence isn't necessarily linear, as Eq. (1) in unequivocal manner (Fletcher and Thomas 2000;Garrone et al 2008).…”
Section: Introductionmentioning
confidence: 99%
“…Activated carbon has hydrophobic sites acting as primary adsorption sites for hydrocarbons mostly in micropores and hydrophilic functional groups as primary sites for water vapor adsorption (Fletcher and Thomas, 2000). During the course of the activation process (particularly chemical activation) the polar functional groups are commonly formed at the edges of graphite planes (Segarra and Glandt, 1994).…”
Section: Introductionmentioning
confidence: 99%
“…. ) covers a wide range of behaviour [16]. In our case, it seems that the evolution of the rate constant at very low relative pressure (<0.02) is different because this is not a peak, only a decrease of the rate constant is observed.…”
Section: Kinetics Of Methanol Adsorption In Static Modementioning
confidence: 53%